The student population of the Cagayan Vallley Institute of Technology a descriptive profile - Sarangay, Lolita (Guzman) 1931- (s.n.], 1969)
The purpose of the study is to develop a profile of the students enrolled in the Cagayan Valley Institute of Technology. The study attempts to describe the kind of student population in terms of personal background, scholastic background and academic performance, and participation in co-curricular activities. The problem which this study purports to describe aims to provide an understanding of the kind of student population enrolled in the Cagayan Valley Institute of Technology and yield valuable information about students' needs and problems.